Airway mucus obstruction triggers macrophage activation and matrix metalloproteinase 12-dependent emphysema - Trojanek, Joanna B.; Cobos-Correa, Amanda; Diemer, Stefanie; Kormann, Michael; Schubert, Susanne C.; Zhou-Suckow, Zhe; Agrawal, Raman; Dürr, Julia; Wagner, Claudius; Schatterny, Jolanthe; Hirtz, Stephanie; Sommerburg, Olaf; et al. (American journal of respiratory cell and molecular biology, 2014)
Whereas cigarette smoking remains the main risk factor for emphysema, recent studies in β-epithelial Na+ channel-transgenic (βENaC-Tg) mice demonstrated that airway surface dehydration, a key pathophysiological mechanism in cystic fibrosis (CF), caused emphysema in the absence of cigarette smoke exposure. However, the underlying mechanisms remain unknown. The aim of this study was to elucidate mechanisms of emphysema formation triggered by airway surface dehydration. We therefore used expression profiling, genetic and pharmacological inhibition, Foerster resonance energy transfer (FRET)-based activity assays, and genetic association studies to identify and validate emphysema candidate genes in βENaC-Tg mice and patients with CF. We identified matrix metalloproteinase 12 (Mmp12) as a highly up-regulated gene in lungs from βENaC-Tg mice, and demonstrate that elevated Mmp12 expression was associated with progressive emphysema formation, which was reduced by genetic deletion and pharmacological inhibition of MMP12 in vivo. By using FRET reporters, we show that MMP12 activity was elevated on the surface of airway macrophages in bronchoalveolar lavage from βENaC-Tg mice and patients with CF. Furthermore, we demonstrate that a functional polymorphism in MMP12 (rs2276109) was associated with severity of lung disease in CF. Our results suggest that MMP12 released by macrophages activated on dehydrated airway surfaces may play an important role in emphysema formation in the absence of cigarette smoke exposure, and may serve as a therapeutic target in CF and potentially other chronic lung diseases associated with airway mucus dehydration and obstruction.
Gesehen am 01.12.2020